Optimization of Lactation Room Management for Vulnerable Groups to Provide Excellent Service at the Mahkamah Syar'iyah Blangkejeren: A Literature Review - Min Adlina; Pandy Muhammad (Abdul Media Literasi, 2024)
The state is obliged to ensure that health services are provided for women, especially family planning (KB) services,pregnancy, childbirth, postpartum or exclusive breastfeeding. It cannot be denied that until now there are still many offices /companies that ignore the existence of lactation rooms. Whereas the obligation of work organizers to provide lactation space has been regulated in the Republic of Indonesia Minister of Health Regulation Number 15 of 2013. The regulation of procedures for providing breastfeeding space aims to provide protection to mothers in exclusive breastfeeding and fulfill children's rights to receive exclusive breastfeeding. The provision of this breastfeeding corner facility is devoted to meeting the needs of mothers and babies who still have to breastfeed, and at the same time aims to increase exclusive breastfeeding for babies as one of the main nutrients. This research discussed about how to optimize the lactation room for vulnerable groups to provide excellent service in Mahkamah Syar’iyah Blangkejeren.